Distributed solar desalination by membrane distillation: current status and future perspectives. (15th June 2021) - Ma, Qiuming; Xu, Zhenyuan; Wang, Ruzhu
Highlights: Advantages of applying MD in small-scale solar desalination are explained Coupled solar-MD research is presented while highlighting the limitations Efforts on performance improvement are rationally categorized and critically reviewed Prioritized future research directions are clearly indicated Abstract: Membrane distillation (MD) has been proven promising in solar-driven desalination. Moreover, its unique characteristics such as simple process, module compactness, high salt rejection rate, etc. allow for a small-scale device in a distributed system. Both theoretical and experimental researches on the coupling between solar collectors and MD aiming at compact and autonomous desalination system have been devoted to enhance freshwater productivity and energy efficiency. In this paper, certain critical gaps are summarized upon a panoramic review of the current status, including limited production and energy performance compared with commercial-scale desalination, unclear relation between solar collecting area and membrane area, and few discussions on efficient condensation, etc. To tackle these challenges, perspectives on the essential future research directions are proposed. Solar direct heating and solar concentration constitute the possible resolution to enhance solar energy utilization for higher water production, which also raise the question of optimizing solar/MD areas. Meanwhile, module stacking, module internal heat recovery and external evaporation heat recovery are deemed prospective in further reducing MD energy consumption. Subsequently, an enhanced vapor condensation needs more exploration. Those aspects and a potential combination among them are the main tasks in the near future, together with more field tests on small distributed solar-driven MD systems. Graphical Abstract: Image, graphical abstract